Increased peripherin in sympathetic axons innervating plantar metatarsal arteries in STZ-induced type I diabetic rats - Johansen, Niloufer J.; Frugier, Tony; Hunne, Billie; Brock, James A. (Frontiers in Neuroscience, 2014)
A common characteristic of axonopathy is the abnormal accumulation of cytoskeletal proteins. We recently reported that streptozotocin (STZ)-induced type 1 diabetes produced a change in the morphology of sympathetic nerve fibers supplying rat plantar metatarsal arteries (PMAs). Here we investigated whether these morphological changes are associated with axonal accumulation of the type III intermediate filament peripherin and the microtubule protein β-tubulin III, as both are implicated in axonal remodeling. PMAs from hyperglycemic STZ-treated rats receiving a low dose of insulin (STZ-LI) were compared with those from normoglycemic STZ-treated rats receiving a high dose of insulin (STZ-HI) and vehicle-treated controls. Western blotting revealed an increase in protein expression level for peripherin in PMAs from STZ-LI rats but no change in that for β-tubulin III. In addition, there was an increase in the number of peripherin immunoreactive nerve fibers in the perivascular nerve plexus of PMAs from STZ-LI rats. Co-labeling for peripherin and neuropeptide Y (a marker for sympathetic axons) revealed that peripherin immunoreactivity increased in sympathetic axons. None of these changes were detected in PMAs from STZ-HI rats, indicating that increased peripherin in sympathetic axons of STZ-LI rats is likely due to hyperglycemia and provides a marker of diabetes-induced nerve damage.